Pelatihan Pemilahan Sampah dan Eco Enzyme Guna Pengembangan dan Menggagas Rumah Kompos Menjadi Wahana Eduwisata Di Gianyar Bali - Permatananda, Pande Ayu Naya Kasih; Pandit, I Gede Suranaya; Dewi, Ni Wayan Erly Sintya; Aryastuti, Anak Agung Sri Agung (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2023)
The government system in Indonesia, the village or ward, is the lowest organizational unit of government. The rural population is the essential capital of development. If the rural population can be fostered as well as possible, then it is hoped that it will become a very valuable human resource for development. In this regard, the government establishes policies, especially in the area of equal distribution of opportunities to obtain education and information for all Indonesians, that are directed at increasing the nation's intelligence and increasing the ability to participate in development activities. Batu Putih Kenek is a village area with a population that is classified as not too dense. Through the latest data obtained from the village office and the results of interviews with the head and village officials, we obtained data on the population of Batu Putih Kenek Village, namely 2,965 people, with details by gender, namely male population = 1,390 people and female population = 1,573. In implementing the village library, many obstacles arise, among them inadequate human resource competence, low public interest in reading, a limited number of collections, and the most dominant problem, the limited budget for the development of the library itself. Even though the library has a significant and strategic role as a partner in supporting the national goal, namely educating the nation's youth, the allocation of funds for library development still needs to be improved. Because this problem is fundamental in nature, it directly impacts all library development programs at all types and levels, especially at the village or ward library level.